Interdisciplinary management of EGFR-inhibitor-induced skin reactions: a German expert opinion - Potthoff, Karin; Hofheinz, Ralf-Dieter; Hassel, Jessica C.; Volkenandt, M.; Lordick, F.; Hartmann, J. T.; Karthaus, M.; Riess, H.; Lipp, H. P.; Hauschild, A.; Trarbach, T.; Wollenberg, A. (Annals of oncology, 2011)
BACKGROUND: Anti-epidermal growth factor receptor treatment strategies, i.e. monoclonal antibodies such as cetuximab and panitumumab, or epidermal growth factor receptor (EGFR) small molecule tyrosine kinase inhibitors, such as erlotinib and gefitinib, have expanded the treatment options for different tumor types. Dermatologic toxic effects are the most common side-effects of EGFR inhibitor therapy. They can profoundly affect the patient's quality of life. - PURPOSE: The aim of this study was to provide interdisciplinary expert recommendations on how to treat patients with skin reactions undergoing anti-EGFR treatment. - MATERIAL AND METHODS: An expert panel from Germany with expertise in medical oncology, dermatology or clinical pharmacology was convened to develop expert recommendations based on published peer-reviewed literature. - RESULTS: The expert recommendations for the state-of-the-art treatment of skin reactions induced by EGFR inhibitor therapy include recommendations for diagnostics and grading as well as grade-specific and stage-adapted treatment approaches and preventive measures. It was concluded that EGFR-inhibitor-related dermatologic reactions should always be treated combining basic care of the skin and a specific therapy adapted to stage and grade of skin reaction. For grade 2 and above, specific treatment recommendations for early- and later-stage skin reactions induced by EGFR-inhibitor therapy were proposed. - CONCLUSION: This paper presents a German national expert opinion for the treatment of skin reactions in patients receiving EGFR inhibitor therapy.
Available online 6 January 2020
Gesehen am 13.01.2023